2022
DOI: 10.3390/s22134984
|View full text |Cite
|
Sign up to set email alerts
|

Towards an Automatic Pollen Detection System in Ambient Air Using Scattering Functions in the Visible Domain

Abstract: Pollen grains strongly affect human health by inducing allergies. Although the monitoring of airborne pollens particles is of major importance, the current measurement methods are manually conducted and are expensive, limiting the number of monitoring stations. Thus, there is a need for relatively low-cost instruments that can work automatically. The possible detection of pollen in urban ambient air (Paris, France) has been reported using the LOAC optical aerosol counter. These measurements indicate that the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Using a 360 • inlet, the ambient air flow is pumped through an optical chamber at a flow of about 15 L•min −1 , and the particles individually cross a laser beam. The scattered light is collected by optical detectors at 4 different scattering angles, 15 • , 60 • , 125 • , 160 • , which allows to partly describe the scattering curves and to retrieve some physical properties of the particles [25]. The measurements at the first angle are almost insensitive to the refractive index of the particles when they are not perfect spheres, thus a direct relation between particle size and scattering intensity can be established during laboratory calibration [34].…”
Section: Beenose Sensormentioning
confidence: 99%
See 1 more Smart Citation
“…Using a 360 • inlet, the ambient air flow is pumped through an optical chamber at a flow of about 15 L•min −1 , and the particles individually cross a laser beam. The scattered light is collected by optical detectors at 4 different scattering angles, 15 • , 60 • , 125 • , 160 • , which allows to partly describe the scattering curves and to retrieve some physical properties of the particles [25]. The measurements at the first angle are almost insensitive to the refractive index of the particles when they are not perfect spheres, thus a direct relation between particle size and scattering intensity can be established during laboratory calibration [34].…”
Section: Beenose Sensormentioning
confidence: 99%
“…A new automated and real-time pollen sensor named Beenose, developed by the Lify-Air company, could cope with these constraints, and could be deployed in dense networks. Beenose is based on light scattered by particles crossing a laser beam in the visible domain, which has been reported to help in distinguishing some pollen families from other ones in several studies [ 24 , 25 , 26 , 27 , 28 , 29 , 30 ]. The same principle has also been used to develop optical counters with typology determination capabilities, to distinguish between anthropogenic pollution particles, natural mineral particles, and pollens [ 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study [ 37 ], we showed that pollens exhibit specific intensity scattering curves allowing their detection among other types of particles and even to distinguish between their various families. In this paper we introduce Beenose, a new small and relatively low-cost pollen sensor that has been developed based on our previous results.…”
Section: Introductionmentioning
confidence: 99%